Originally Posted by

**Jones** Hi,

The laws of logarithms are pretty confusing to me.

I have the following problem:

$\displaystyle \frac{1}{2^x} = \frac{5}{8^{x+3}}$

This can be rewritten as $\displaystyle 2^{-x} = 5*8^{-(x+3)}$

if you log both sides you'll get: $\displaystyle -xln2 = ln5*-(x+3)ln8$

so when we have a multiplication like this -(x+3)*ln8 does this imply addition?

I don't understand the basic arithmetic operations seem to have been switched, just to maximize confusion.

Someone please explain how this works =/

Jones